New possibilities in drug therapy of post-stroke aphasia - V. N. Shishkova; L. I. Zotova; N. G. Malyukova; N. V. Kan; E. M. Gasanova; V. S. Kalacheva; M. A. Kudryashova (Лечащий Врач)
Approaches to rehabilitation of patients with post-stroke aphasia of different severity levels were studied. Dynamics of speech and other cognitive function restoration on the background of complex therapy including cholinesterase inhibitor was studied in patients who suffered from first ischemic stroke in the left cerebral hemisphere.